SURFACE TOPOGRAPHY AND INTERNAL STRAIN VARIATION IN WIDE HOT OROGENS FROM THREE-DIMENSIONAL ANALOGUE AND TWO-DIMENSIONAL NUMERICAL VICE MODELS - Cruden A.R.; Nasseri M.H.B.; Pysklywec R. (My University, 2006)
The post-accretionary deformation of wide, hot orogens is characterized by pure-shear or transpressional shortening of relatively weak lithosphere (the orogen) between converging stronger blocks (the vice). We report on a series of analogue vice models and compare the resulting three-dimensional strain fields and surface topographies to equivalent two-dimensional numerical experiments. In the analogue models a rheologically stratified (frictional/viscous) weak orogenic lithosphere overlying a viscous asthenosphere is squeezed between converging strong lithospheric blocks. Ductile lower crust and mantle in the weak lithosphere is free to flow laterally, parallel to the orogen. The Argand number describes the model dynamics and strongly controls both the orogenic relief and the degree of lower crustal orogen parallel stretching in the analogue models. Cross sections of numerical and analogue experiments display consistent geometries in which upper crustal deformation is characterized by upright folding compared to apparently decoupled horizontal strains in the lower crust. The relative buoyancy and degree of orogen parallel flow in the lower crust of the analogue models has a dramatic influence on three-dimensional strain fields and the kinematics of upper crustal curvilinear shear zones. The analogue and numerical results demonstrate the importance of three-dimensional effects in determining the structure of natural orogens and compare favourably to field and geophysical observations of large hot orogens in the geological record. © The Geological Society of London 2006.